The Sadler's Wells dialogues (1772-1780) - Dibdin, Charles 1745-1814 (Artaria Editions, 2007)
This is a collection of short operatic works composed by Dibdin in the 1770s for the theatre at Sadler's Wells, near Islington: 1. The palace of mirth. 2. The brickdust man. 3. The ladle. 4. The grenadier. 5. The mischance. - With a foreword, introduction and commentary. - Two appendices: The first appendix contains 15 further, incomplete works.